Software implementation of artificial neural networks in automated intelligent systems - Харченко, В.П.; Алєксєєв, О.М. (Proceedings of National Aviation University (archive), 2009)
Application of neural networks technologies effectively decides the task of synthesis of origin of accident risk and gives out the vector of managing signals of network on incomplete and distorted information about the phenomena, events and processes which influence on safety flights.